Antipsychotic-induced bone loss: the role of dopamine, serotonin and adrenergic receptor signalling - Weerasinghe, D. Kavindi; Hodge, Jason M.; Pasco, Julie A.; Samarasinghe, Rasika M.; Azimi Manavi, Behnaz; Williams, Lana J. (Frontiers in Cell and Developmental Biology, 2023)
Antipsychotics are commonly used in treating psychiatric disorders. These medications primarily target dopamine the serotonin receptors, they have some affinity to adrenergic, histamine, glutamate and muscarinic receptors. There is clinical evidence that antipsychotic use decreases BMD and increases fracture risk, with dopamine, serotonin and adrenergic receptor-signalling becoming an increasing area of focus where the presence of these receptors in osteoclasts and osteoblasts have been demonstrated. Osteoclasts and osteoblasts are the most important cells in the bone remodelling and the bone regeneration process where the activity of these cells determine the bone resorption and formation process in order to maintain healthy bone. However, an imbalance in osteoclast and osteoblast activity can lead to decreased BMD and increased fracture risk, which is also believed to be exacerbated by antipsychotics use. Therefore, the aim of this review is to provide an overview of the mechanisms of action of first, second and third generation antipsychotics and the expression profiles of dopamine, serotonin and adrenergic receptors during osteoclastogenesis and osteoblastogenesis.